Analysis of Rainfall Characteristics using Hydrognomon v.4.0 in Karangploso, Malang - Triawati, Indri; Ali, Atif Muhammad; Palupi, Retno; Richard, Hendrik; Hariadi, Agung; Mahmud, Mahmud; Pratama, Raditya; Habiburrahman , Novan (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2024)
Rainfall is hydrology event that occurred seasonal in every year. There are two seasons occurred in Indonesia, dry season and rainy season. The analysis of rainfall characteristics plays a significant role to predict the rainfall occurrence and probability of flash flood. In this paper, rainfall analysis using Hydrognomon v.4.0 will provide hydrology data information, such as rainfall intensity and time series. The highest maximum rainfall of 526 mm (in 2010) has a return period of about 11 years. This means that rainfall of this magnitude can be expected to occur once every 11 years. The maximum rainfall of 425 mm (2013) has a return period of about 5.5 years, indicating a more frequent occurrence than the highest rainfall. Thus, it makes data trend rainfall with higher values tends to have longer return periods, indicating infrequent intensity. However, rainfall with lower intensity tends to have shorter return periods and occurring more frequently.